Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Yang Terdaftar di BEI 2013-2015) - Hartono, Rengga Sukma; , Drs. Suyatmin Waskito Adi, M.Si (2016)
IMPACT INVESTMENT DECISION, FINANCING DECISION, DIVIDEN POLICY, AND MANAGERIAL OWNERSHIP TO THE FIRM VALUE The purpose of this study is to analyze the impact investment decision, financing decision, dividen policy, and managerial ownership to the firm value. Investment decision was measured by Book Value of Assets (BVA). Financing decision was measured by Debt to Equity Ratio (DER). Dividend policy was measured by Dividend Payout Ratio (DPR). Managerial ownership was measured by proportion of share ownership by the managerial side. Firm value was measured by Price Book Value (PBV). The population in this research is the manufacturing companies listed on the Indonesia Stock Exchange and is continuously published the annual report in the year 2013-2015. The sample obtained was 63 observation using purposive sampling method. Data analysis technique uses classic assumption test and Hypothesis test uses multipleregression analysis. The results of this research indicate that the investment decision no significant positive effect on the firm value, financing decision significant negative effect on the firm value, dividend policy significant negative effect on the firm value. While the managerial ownership significant positive on the fim value.